Patient‐reported outcome measures in advanced musculoskeletal physiotherapy practice: a systematic review. (29th June 2017) - Fennelly, Orna; Blake, Catherine; Desmeules, François; Stokes, Diarmuid; Cunningham, Caitriona
Abstract: Objective: Advanced practice physiotherapists (APPs), also known as extended scope physiotherapists, provide a new model of service delivery for musculoskeletal (MSK) disorders. Research to date has largely focused on health service efficiencies, with less emphasis on patient outcomes. The present systematic review aimed to identify the patient‐reported outcome measures (PROMs) being utilized by APPs. Method: A wide search strategy was employed, including the PubMed, Embase, CINAHL, CENTRAL and PEDro databases, to identify studies relating to PROMs utilized by APPs in MSK healthcare settings. PROMs identified were classified into predetermined outcome domains, with additional contextual data extracted. Results: Of the initial 12, 302 studies, 38 met the inclusion criteria. These involved APPs across different settings, utilizing 72 different PROMs and most commonly capturing: Patient Satisfaction, Quality of Life (QoL), Functional Status, and Pain; and, less frequently: Global Status (i.e. overall improvement), Psychological Well‐Being, Work ability, and Healthcare Consumption and Costs. The quality of the PROMs varied greatly, with Satisfaction most commonly measured utilizing non‐standardized locally‐devised tools; the EuroQol five‐dimensions questionnaire (EuroQoL‐5D) and 36‐Item Short‐Form (SF‐36) cited most frequently to capture QoL; and the Visual Analogue Scale (VAS) to capture Pain. No key measure was identified to capture Functional Status, with 15 different tools utilized. Conclusion: APPs utilized a multiplicity of PROMs across a range of MSK disorders. The present review will act as an important resource, informing the selection of outcomes for MSK disorders, with a view to greater standardization of outcome measurement in MSK clinical practice, service evaluation and research.